2009
DOI: 10.1080/02705060.2009.9664319
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Variation in Stable Isotopes of Carbon and Nitrogen in Lake Carl Blackwell, Oklahoma

Abstract: A survey of stable isotopes of carbon (C) and nitrogen (N) for water, plankton, and sediments and associated limnological parameters was conducted in 2006-2007 in Lake Carl Blackwell, Oklahoma. The effects of time and station were assessed to serve as the basis of further studies that would identify plant sources for consumers and describe the food web of this turbid lake. Samples of water and plankton were taken at four stations along an east to west thalweg; sediments were obtained at four additional station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Furthermore, recent studies have shown that stable isotopes vary among habitats within and among lakes (Cabana and Rasmussen 1996;Vander Zanden and Rasmussen 1999;Post 2002;Syvaranta et al 2006;Toetz et al 2009). Stable N isotope also has been found to vary seasonally in POM (Gu 2009), mussels (Gustafson et al 2007), and aquatic invertebrates (Woodland et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent studies have shown that stable isotopes vary among habitats within and among lakes (Cabana and Rasmussen 1996;Vander Zanden and Rasmussen 1999;Post 2002;Syvaranta et al 2006;Toetz et al 2009). Stable N isotope also has been found to vary seasonally in POM (Gu 2009), mussels (Gustafson et al 2007), and aquatic invertebrates (Woodland et al 2012).…”
Section: Introductionmentioning
confidence: 99%